1998
DOI: 10.1073/pnas.95.17.9973
|View full text |Cite
|
Sign up to set email alerts
|

A high throughput screen to identify secreted and transmembrane proteins involved in Drosophila embryogenesis

Abstract: Secreted and transmembrane proteins play an essential role in intercellular communication during the development of multicellular organisms. Because only a small number of these genes have been characterized, we developed a screen for genes encoding extracellular proteins that are differentially expressed during Drosophila embryogenesis. Our approach utilizes a new method for screening large numbers of cDNAs by whole-embryo in situ hybridization. The cDNA library for the screen was prepared from rough endoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(63 citation statements)
references
References 24 publications
6
56
0
1
Order By: Relevance
“…As expected, the cytosol fraction was highly enriched in mRNAs encoding cytosolic proteins (EASE value > 8e À8 ). Consistent with previous studies on mRNA partitioning between cytosol and membrane compartments, we observed a partial, but substantial, overlap of cytosolic mRNAs in the nuclear envelope pool (Kopczynski et al 1998;Diehn et al 2000Diehn et al , 2006de Jong et al 2006). Of the 11,386 genes identified in the cytosol fractions, 9263 of these messages were also detected at significant (more than twofold over background) levels in the nuclear envelope fraction.…”
Section: à12supporting
confidence: 78%
See 1 more Smart Citation
“…As expected, the cytosol fraction was highly enriched in mRNAs encoding cytosolic proteins (EASE value > 8e À8 ). Consistent with previous studies on mRNA partitioning between cytosol and membrane compartments, we observed a partial, but substantial, overlap of cytosolic mRNAs in the nuclear envelope pool (Kopczynski et al 1998;Diehn et al 2000Diehn et al , 2006de Jong et al 2006). Of the 11,386 genes identified in the cytosol fractions, 9263 of these messages were also detected at significant (more than twofold over background) levels in the nuclear envelope fraction.…”
Section: à12supporting
confidence: 78%
“…Analyses of mRNA partitioning between the cytosol and ER membrane compartments of mammalian cells, fly, and yeast have identified cohorts of cytosolic/nucleoplasmic protein-encoding mRNAs that are highly enriched in the ER, suggesting that ER-directed mRNA localization can occur by a mechanism(s) other than the SRP pathway (Mueckler and Pitot 1981;Kopczynski et al 1998;Diehn et al 2000;Nicchitta et al 2005). In support of this proposal, it has been demonstrated that mRNAs retain their association with the ER in the absence of ribosome engagement and thus participate in ribosome-independent interactions with components of the ER Lerner and Nicchitta 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Future screens could also combine the strategies of genetic mutation and spatial selection of follicle cells, for example by crossing GAL4 lines and UAS-GFP into a grkϪ background and analyzing the effect of grk on the expression profiles of specific subregions of the follicular epithelium. This type of targeted mutant analysis will likely be the most useful future application of these methods-screens for purely spatial selection may be supplanted by large-scale in situ screening (37), but it is unlikely to become feasible to perform many thousands of in situ hybridizations for every mutant situation a researcher wishes to analyze. These methods can also be readily applied to other systems; Drosophila imaginal discs are an obvious candidate, and as Krasnow et al (5) have previously pointed out, FACS purification of cells marked with cell type-specific reporter constructs can in principle be applied to any organism receptive to germ-line transformation.…”
Section: Dc9mentioning
confidence: 99%
“…We first identified btsz in a reverse genetic screen for genes expressed during Drosophila development (18). The btsz transcription unit covers Ϸ50 kb and is predicted to have at least 15 exons (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All cDNAs were isolated by screening Drosophila embryonic (LD) and adult head (GH) cDNA libraries (17) with probes derived from clones from the CK cDNA library (18) and by 5Ј RACE, which was accomplished by using the Clontech Marathon cDNA amplification kit. Potential full-length cDNAs were sequenced, analyzed with SEQUENCHER software, and searched against nucleotide and protein databases by using BLAST programs (19).…”
Section: Methodsmentioning
confidence: 99%